Extensión del área de distribución de Sturnira koopmanhilli McCarthy et al. 2006 en Colombia - Martínez-Arias, Víctor M.; Solari, Sergio (THERYA, 2013)
As a result of our research on Sturnira in biological collections, we present a noteworthy range extension for S. koopmanhilli. The distribution of this taxon, has been previously suggested to be associated to the Biogeographic Chocó, in Colombia and Ecuador (especially related to the occidental Andean slope). The specimens we report not only confirm this geographic pattern, but also extends the specieâ€™s distribution to the north of the Colombian Central Cordillera, revealing a connectivity between the Nechí biogeographic district and the Chocó Region, a pattern also recorded for other mammal and vertebrate groups. Additionally, it is important to highlight that the current range of the species is located within the regions with the highest deforestation rates in Colombia, which in combination with its low representation in museum collections and the absence of ecological knowledge, show the need for a wider sample in order to determinate the actual speciesâ€™ threat level. Keywords: Andes, Choco, Distribution, Morphology, Sturnira.